Churches of Ani in the Context of Armenian-Georgian Architectural Interrelations of the Second Half of the 10th – First Half of the 11th Century: Addressing the Problem - Kazaryan, Armen Yu.; Baeva , Olga V. (Actual Problems of Theory and History of Art, 2024)
The article aims to open a new page in the study of the interrelations between the medieval architectural traditions of Armenia and Georgia and identify ways to solve the narrower problem of the interaction of these traditions in the era of the flourishing of the Armenian capital Ani and the construction of the largest cathedrals in Georgia. A small number of comparisons of architectural plans and individual decorative forms of monuments of Ani and Georgian churches of the second half of the 10th – first half of the 11th century demonstrate similarities of forms that could be the result not only of common roots in the architecture of the 7th century, and not only of parallel paths of development in the Middle Ages, but also of active and intensive contacts between representatives of the elites and master builders of the two neighboring countries. The research focuses on both the typology of the churches and individual architectural details. The comparison of the scales and images of the Tayk’s (Tao) cathedrals, the structure of the interior forms of Samtavro in Mtskheta with the interior features of the Ani Cathedral proved fruitful. The similarity of some details, such as the combined squinch-pendentive underdome transitions, pseudo-Ionic capitals, the design of conch niches with a special type of shells, as well as the unusual completion of small facade niches in Armenian and Georgian buildings, leads to the conviction of a variety of manifestations of the exchange of architectural ideas. The results obtained are preliminary, they open up the possibility for a more detailed study of this topic, which requires a careful selection of graphic material and a thoughtful analysis. The study has been realized by the grant of the Russian Science Foundation, project no. 22-18-00354, https://rscf.ru/project/22-18-00354/, in the Moscow State University of Civil Engineering (MGSU), National Research University.